Posttraumatic growth among breast cancer survivor after underwent mastectomy - Putri, Kadek Sunita Winayaka; Suarya, Luh Made Karisma Sukmayanti (Talenta Publisher, 2024)
Cancer and the mastectomy procedure experienced by individuals with breast cancer can be a traumatic experience. The traumatic experience can affect the physical, psychological, and sexual quality of life of individuals. However, this traumatic event can trigger posttraumatic growth in some cancer survivors. This paper will explain posttraumatic growth among cancer survivors who have undergone mastectomy. We will describe some stages, indicators, and driving factors of posttraumatic growth in post-mastectomy cancer survivors. This review can help intervention programs to improve posttraumatic growth among post-mastectomy breast cancer survivors.